2017
DOI: 10.1016/j.jspd.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Rod lengthening with the magnetically controlled growing rod: factors influencing rod slippage and reduced gains during distractions

Abstract: Introduction: Ability to achieve successful MCGR distraction is crucial for gradual spine lengthening. Rod slippage has been described as a failure of internal magnet rotation leading to a slippage and an inability to distract the rod. However, its onset, significance and risk factors are currently unknown. In addition, how this phenomenon pertains to actual distracted lengths is unknown. Hence, the aims of this study are to identify the factors that are associated with rod slippage and to study the pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 21 publications
2
48
0
2
Order By: Relevance
“…We found higher distraction rates in the first-year results (13 mm/year) compared to the distraction rate in the period from 1 year until last follow (7 mm/year distraction). This supports our general impression of diminishing returns with the MCGR over time [21,22]. Whether our protocol of distraction every 3 months up to stalling of the actuator is the most optimal to prevent diminishing returns remains to be determined.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We found higher distraction rates in the first-year results (13 mm/year) compared to the distraction rate in the period from 1 year until last follow (7 mm/year distraction). This supports our general impression of diminishing returns with the MCGR over time [21,22]. Whether our protocol of distraction every 3 months up to stalling of the actuator is the most optimal to prevent diminishing returns remains to be determined.…”
Section: Discussionsupporting
confidence: 79%
“…They found that length gains decreased with every additional lengthening over time. More recently, Cheung et al found similar reduced lengthenings with MCGR [22]. We found higher distraction rates in the first-year results (13 mm/year) compared to the distraction rate in the period from 1 year until last follow (7 mm/year distraction).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…One explanation was that the bending moment on the telescopic bar was increased as the rods extended, leading to severer 'offaxis loading' and material loss. This may explain the frequent 'diminishing returns' or slippage during distraction observed in rods reaching half of the maximum extendable length [19,20] and the angulated telescopic bars noticed on radiographs [21]. Besides, it has been suggested that a single rod construct was subjected to a higher bending moment and therefore at a higher risk of breakage [22].…”
Section: Discussionmentioning
confidence: 99%
“…55,57,59]. В среднем исходное расстояние составляло 180 мм, сразу после первой операции -200 мм, в конце ХИРУРГИЯ ПОЗВОНОЧНИКА 2020.…”
unclassified